COMPARISON OF FINANCIAL PERFORMANCE BETWEEN PRIVATE AND STATE-OWNED COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE, 2021–2024 - Dede Pramurza (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Financial performance refers to the financial results or achievements achieved by a company in a certain period, which reflects the level of effectiveness and efficiency in managing financial resources to achieve company goals. This study aims to determine whether there are differences in financial performance between Private Commercial Banks and State-Owned Commercial Banks (BUMN) using several financial ratios, ROA, NIM, BOPO, CAR, and NPL during the 2021–2024 period. The sample in this study was selected using a purposive sampling method. The type of data used is secondary data, and data was collected through documentation techniques. The analytical tool used is descriptive statistical analysis, while the analytical method used is the Independent Samples t-Test. The results of the study indicate that Private Banks show better financial performance than State-Owned Banks, and there is a significant difference in the CAR between Private Commercial Banks and State-Owned Commercial Banks. However, there is no significant difference between Private Banks and State-Owned Banks in terms of ROA, NIM, BOPO, and NPL.